2019
DOI: 10.1017/s1460396919000153
|View full text |Cite
|
Sign up to set email alerts
|

A review of applications of principles of quantum physics in oncology: do quantum physics principles have any role in oncology research and applications?

Abstract: Background:Research in the applications of the principles of quantum physics in oncology has progressed significantly over the past decades; and several research groups with professionals from diverse scientific background, including electrical engineers, mathematicians, biologists, atomic physicists, computer programmers, and biochemists, are working collaboratively in an unprecedented and pioneering economic, organisational and human effort searching for a wider and more effective, potentially definitive, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 87 publications
(270 reference statements)
0
10
0
Order By: Relevance
“…Recently it has been concluded that fields such as oncology, biology and chemistry could greatly benefit from application of principles of quantum physics in order to provide new perspectives and greater insights into cancer. This has the potential to lead to deeper understanding of cancers and the potential for more effective and personalized treatments [86] . Applying concepts of quantum mechanics to trying to understand why cells might develop oncogenic mutations, as cells may become cancerous as a way to increase their entropy as proposed by Laster et al who proposed this based on combining the uncertainties of genetic changes as expressed by epigenetic changes and/or somatic mutations with the uncertainties of environmental changes [87] .…”
Section: Cancer and Quantum Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been concluded that fields such as oncology, biology and chemistry could greatly benefit from application of principles of quantum physics in order to provide new perspectives and greater insights into cancer. This has the potential to lead to deeper understanding of cancers and the potential for more effective and personalized treatments [86] . Applying concepts of quantum mechanics to trying to understand why cells might develop oncogenic mutations, as cells may become cancerous as a way to increase their entropy as proposed by Laster et al who proposed this based on combining the uncertainties of genetic changes as expressed by epigenetic changes and/or somatic mutations with the uncertainties of environmental changes [87] .…”
Section: Cancer and Quantum Mechanicsmentioning
confidence: 99%
“…The potential applications of the principles of quantum physics in oncology have been demonstrated in several areas. Significant advancements in oncology research have been achieved through modelling of concepts such as quantum metabolism, quantum biology, quantum chemistry, quantum biochemistry, and quantum entropy, which have been used to provide new insights into the origin of cancer cells and their rapid, uncontrolled rates of cell division [86] . Quantum theory has been shown to be relevant for developing models with the potential to explain cancer related biological and biochemical processes cancer including the effects of carcinogens on DNA, the mechanism of interactions of chemotherapy drugs with genetic material [89] ; as well as the understanding of DNA mutations and defective protein synthesis [90] .…”
Section: Cancer and Quantum Mechanicsmentioning
confidence: 99%
“…Although at present the existing computing power and the complexity surrounding the simulations of QM is a major drawback, the development of quantum computers can drastically reduce the computational time and improve the use of QM. 144 Machine Learning/Artificial Intelligence Artificial intelligence (AI) is a branch of computer science with multiple applications in various fields of study that acquire novel information, define decision making, and design novel methods. 145 AI is being rapidly introduced in health care as it has numerous advantages in the field of drug development.…”
Section: Systems Pharmacologymentioning
confidence: 99%
“…1 The traditional therapeutic modalities for cancers are mainly surgery, chemotherapy and radiation therapy; and more recently immunotherapy, hormone therapy and targeted therapy have become commonplace for some cancer treatments. In the past few years, there have been growing investigations towards personalised and targeted treatment options for cancer patients including gene therapy, 2 use of quantum physics principles to understand and treat cancer, 3 use of functionalised gold nanoparticles for cancer therapy, 4 the use of ultrasound-mediated microbubbles for drug delivery and combining imaging genomics and radiation genomics. 68 The ultrasoundmediated microbubble technique used as a non-invasive delivery of therapeutic agents for cancer treatment has recently evolved as one of the advanced therapeutic methods for personalised and targeted cancer treatment.…”
Section: Introductionmentioning
confidence: 99%